Intravascular Ultrasound in the Endovascular Treatment of Patients With Peripheral Arterial Disease: Current Role and Future Perspectives - Loffroy, Romaric; Falvo, Nicolas; Galland, Christophe; Fréchier, Léo; Ledan, Frédérik; Midulla, Marco; Chevallier, Olivier (Frontiers in Cardiovascular Medicine, 2020)
Over the last decade, intravascular ultrasound (IVUS) has emerged as a useful and often necessary adjunctive tool to angiography in an increasing number of catheter-based procedures for peripheral arterial disease (PAD). IVUS catheters offer accurate cross-sectional imaging of arterial vessels with high dimensional accuracy and provide detailed information about lesion morphology. IVUS enables assessment of the vessel size, plaque morphology and the presence of dissections. Furthermore, IVUS is able to guide the optimal choice of appropriate percutaneous transluminal angioplasty (PTA) technique, guide the delivery of endovascular devices, and assess the immediate outcome of an intervention. In this review, we discuss the role of IVUS for PAD, specifically the applications of IVUS technology during interventional procedures including PTA, stent sizing, crossing total occlusion, assessing residual narrowing and stent apposition and expansion, and atherectomy. Future perspectives of IVUS-guided treatments and cost-effectiveness of the routine use of IVUS during vascular procedures will be also discussed.